Sustained ameliorating effects and autonomic mechanisms of transcutaneous electrical acustimulation at ST36 in patients with chronic constipation - Zhou, Jie-Yi; Wang, Jian; Ning, Bei-Fang; Hu, Ye-Dong; Zhao, Qi; Tan, Wei; Shi, Pei-Mei; Yuan, Zong-Li; Feng, Xin-Wei; Chen, Jiande D. Z.; Xie, Wei-Fen (Frontiers in Neuroscience, 2022)
Background and aims The treatment of chronic constipation is still a great challenge in clinical practice. This study aimed to determine the efficacy and sustained effects of transcutaneous electrical acustimulation (TEA) at acupoint ST36 on the treatment of chronic constipation and explore possible underlying mechanisms. Methods Forty-four patients with chronic constipation were recruited and randomly assigned to a TEA group or sham-TEA group. A bowel diary was recorded by the patients. The Patient Assessment of Constipation Symptom (PAC-SYM) and the Patient Assessment of Constipation Quality of Life (PAC-QoL) questionnaires were administered during each visit. Anal and rectal functions were evaluated with anorectal manometry. Autonomic functions were assessed by the special analysis of heart rate variability derived from the ECG recording. Results Compared with sham-TEA, 2-week TEA treatment significantly increased the number of spontaneous bowel movements (SBMs) (5.64 ± 0.54 vs. 2.82 ± 0.36, P < 0.001) and lowered the total scores of PAC-SYM (0.90 ± 0.14 vs. 1.35 ± 0.13, P < 0.001) and PAC-QoL (0.89 ± 0.13 vs. 1.32 ± 0.14, P < 0.05). TEA improved symptoms, as reflected by a reduction in the straining (P < 0.001), the incomplete defecation (P < 0.05), the frequency of emergency drug use (P < 0.05), the days of abdominal distension (P < 0.01) and an increase in intestinal satisfaction (P < 0.01). Interestingly, the effects of TEA on the improvement of weekly SBMs sustained four weeks after the cessation of treatment (P < 0.001). Anorectal manometry indicated that 2-week treatment of TEA lowered the threshold of first sensation (P < 0.05), desire of defecation (P < 0.01) and maximum tolerable volume (P < 0.001) compared with sham-TEA group. TEA also significantly enhanced vagal activity, reflected by high-frequency band of heart rate variability, compared with sham-TEA (57.86 ± 1.83 vs. 48.51 ± 2.04, P < 0.01). Conclusion TEA ameliorates constipation with sustained effects, which may be mediated via improvement of rectal sensitivity and enhancement of vagal activity. Clinical trial registration [https://clinicaltrials.gov/], identifier [ChiCTR210004267].